Long-Term Outcomes of Thyroid Cryoablation in Rats With Model of Diffuse Hyperplasia - Pobelensky, Kostiantyn; Legach, Evgen (Problems of Cryobiology and Cryomedicine, 2020)
Probl Cryobiol Cryomed 2020; 30(3): 285